2017
DOI: 10.1007/s12079-017-0394-6
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial intelligence: imitation games, time-sharing, and long-range quantum coherence

Abstract: Bacteria are far more intelligent than we can think of. They adopt different survival strategies to make their life comfortable. Researches on bacterial communication to date suggest that bacteria can communicate with each other using chemical signaling molecules as well as using ion channel mediated electrical signaling. Though in past few decades the scopes of chemical signaling have been investigated extensively, those of electrical signaling have received less attention. In this article, we present a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Initially, primitive cells interacted with their environment in a limited manner in continuing compliance with the First Laws of Physiology (Torday and Rehan, 2012). Since evolution can be defined as the aggregate of its communications directed towards problem-solving (De Loof, 2015a), it might be surmised that the reciprocating complexity of cellular networks may have arisen as a defensive mechanism against the organized pseudo-multicellular behaviors of bacteria, such as quorum sensing (Castillo-Juárez et al, 2015) and biofilm (Majumdar and Pal, 2017). This coordinate problem solving by the three cellular forms (Bacteria, Archeae, Eukaryota), would have provided complementary, interdependent interchanges that gradually gave rise to the complex physiologic traits of multicellular organisms.…”
Section: The First Principles Of Physiology and Cell-cell Communicmentioning
confidence: 99%
“…Initially, primitive cells interacted with their environment in a limited manner in continuing compliance with the First Laws of Physiology (Torday and Rehan, 2012). Since evolution can be defined as the aggregate of its communications directed towards problem-solving (De Loof, 2015a), it might be surmised that the reciprocating complexity of cellular networks may have arisen as a defensive mechanism against the organized pseudo-multicellular behaviors of bacteria, such as quorum sensing (Castillo-Juárez et al, 2015) and biofilm (Majumdar and Pal, 2017). This coordinate problem solving by the three cellular forms (Bacteria, Archeae, Eukaryota), would have provided complementary, interdependent interchanges that gradually gave rise to the complex physiologic traits of multicellular organisms.…”
Section: The First Principles Of Physiology and Cell-cell Communicmentioning
confidence: 99%
“…It has been observed that some Gram positive and Gram negative bacteria live in organized communities [1]. This bacterial communities are glued together by extracellular polymeric substance (EPS), which is called a biofilms [2]. Bacteria in biofilm communities can communicate to each other in two different ways.…”
Section: Introductionmentioning
confidence: 99%
“…When a thresh-old concentration of the signaling molecules is achieved, a coordinated change in bacterial collective behavior is initiated. This bacterial collective behavior is known as quorum sensing by which bacterial cell integrate in order to determine their optimal survival stagey [1,2]. Quorum sensing coordinate the gene expression, when the bacterial cell population has reached a high cell density.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations